2008
DOI: 10.1007/s10641-008-9392-0
|View full text |Cite
|
Sign up to set email alerts
|

Offspring number in a livebearing fish (Poecilia mexicana, Poeciliidae): reduced fecundity and reduced plasticity in a population of cave mollies

Abstract: Life history traits within species often vary among different habitats. We measured female fecundity in mollies (Poecilia mexicana) from a H 2 S-rich cave and from a neighbouring surface habitat, as well as in laboratory-reared individuals of both populations raised in either light or continuous darkness. Compared to conspecifics from surface habitats, cave-dwelling P. mexicana had reduced fecundity (adjusted for size) in the field. In the laboratory, the fecundity of surface mollies was higher in light than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…Even if reared in the laboratory under benign ad libitum-food conditions (where we might expect cave mollies to maximize incipient matrotrophy according to Trexler and DeAngelis 2003;see also Marsh-Matthews and Deaton 2006) the initial maternal investment in yolk is still much greater than in surface mollies, which points to a genetic component to offspring size in cave mollies. In concordance with this, Riesch et al (2009b) demonstrated a genetically inherited reduction in cave molly fecundity relative to surface mollies, but argued that this likely reflects selection for larger eggs, as would be predicted by a resource-dependent advantage of matrotrophy (Trexler and DeAngelis 2003). On the other hand, if nutrient transfer in the cave molly continued over a longer gestation time (see above), total matrotrophic investment per offspring might even be greater in the cave molly.…”
Section: Discussionmentioning
confidence: 77%
“…Even if reared in the laboratory under benign ad libitum-food conditions (where we might expect cave mollies to maximize incipient matrotrophy according to Trexler and DeAngelis 2003;see also Marsh-Matthews and Deaton 2006) the initial maternal investment in yolk is still much greater than in surface mollies, which points to a genetic component to offspring size in cave mollies. In concordance with this, Riesch et al (2009b) demonstrated a genetically inherited reduction in cave molly fecundity relative to surface mollies, but argued that this likely reflects selection for larger eggs, as would be predicted by a resource-dependent advantage of matrotrophy (Trexler and DeAngelis 2003). On the other hand, if nutrient transfer in the cave molly continued over a longer gestation time (see above), total matrotrophic investment per offspring might even be greater in the cave molly.…”
Section: Discussionmentioning
confidence: 77%
“…Each rearing tank thus only contained siblings from the same clutch. To avoid stress for the fish we did not measure offspring size, but the fact that cave mollies produce considerably larger offspring has repeatedly been demonstrated in the field and under similar common garden conditions (e.g., Riesch et al 2009bRiesch et al , 2010a, and cave molly offspring were visibly larger in the present experiment. After 30 days, the experiment was terminated and we calculated 'offspring survival' (number of surviving offspring relative to the original clutch size) for each brood.…”
Section: Methodsmentioning
confidence: 75%
“…Therefore, given the heritability of the population differences in the reproductive traits investigated here (Riesch et al , 2010d, and assuming roughly equal interbrood intervals and total life-spans (R. Riesch, unpubl. data), this suggests that cave molly females may also have lower reproductive fitness than resident surface molly females if they managed to successfully migrate into the adjacent benign surface habitats, and thus, would potentially be out-competed by the surface ecotype (for in-depth discussion on the benefits of larger offspring size in extreme habitats see Riesch et al 2009bRiesch et al , 2010a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated male preference for larger females in many species (Abrahams, 1993; Bisazza, Marconato & Marin, 1989; Dosen & Montgomerie, 2004a; Gumm & Gabor, 2005; Herdman, Kelly & Godin, 2004; Hoysak & Godin, 2007; Jeswiet & Godin, 2011; Plath et al, 2006; Ptacek & Travis, 1997). This is likely a result of the strong correlation between female size and fecundity (Herdman, Kelly & Godin, 2004; Hughes, 1985; Marsh-Matthews et al, 2005; Milton & Arthington, 1983; Reznick & Endler, 1982; Riesch et al, 2009b), suggesting that size is used as a signal of female quality and has played a role in the evolution of male mate choice.…”
Section: Introductionmentioning
confidence: 99%